15.3: A Novel Liquid Crystal Lens for Autostereoscopic 3D Display. Issue 1 (1st July 2013) - Liu, Sheng‐Chi; Yang, Po‐Sen; Sun, Yi‐Lin; Tsai, Yung‐Sheng; Tung, Jen‐Lang
Abstract This work proposes a novel LC lens to achieve an autostereoscopic 2D/3D display. The optimized design parameters of the LC lens are derived by a new theoretical analysis. Based on the experimental results, the LC lens demonstrates high focus‐tunable capability, the particular lens performance, and most notably without inducing disclination line during operating.